(3TQM GdUfGYI GdUZjQI dLGdjfhSs - (3CHh GdMSf Ydj Hf QVhGf Hf Ydj Hf LYaQ GdWHjH GdeUQjs
(3ChdgG (B:s
(3bUOfG Cf fVY cdGekG TGQMkG deG CSJZdb ef cJGH LGdjfhS ai cJGHg GdeSei GdUfGYI GdUZjQI afbhd (B: (3Ef LGdjfhS Sei gPG ddUfYI GdUZjQI ,djOd gPG GdGSe Ydi Cf GdcJGH jJVef bhGfjf UfGYI GdWH s
(3BNQgG (B:s
(3Ydi gPG GdSHjd jfHZi Cf JYde CZQGV LGdjfhS , hJYed YfG UfGYI GdWH , Ydi CceGd eG jchf Ef TGA Gddg s
(3cJHJ HNW CfOdSi eGYOG GdcQGSGJ GdChdis
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B130 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1082s
(3eUOQ GbJfGA GdCUd (B:s
(3GdESchQjGd (B(883) s
Keywords: (3GdWHs